Hospitalar Morbidity In Traffic Accident In Pernambuco - Fernandes, Flávia Emília Cavalcante Valença (2019)
The objective of this study was to evaluate hospital morbidity due to traffic accident in Pernambuco between 2007 and 2012, grouping the results by sex and age. A descriptive quantitative study was carried out, being data retrieved from SUS’ Hospital Information System and treated by means of the statistical program gretl and Stata12. The research was approved by the Ethics Committee under the number CAAE: 36271414.9.0000.5207. The average hospitalization rate for men was 43.33 per 100 thousand and of 9.67 per 100 thousand for women, being the age group between 20 and 29 years old the most affected for both sexes. As for the elderly, the hospitalization rate rose from 8.03 per 100 thousand in 2007 to 45.09 per 100 thousand in 2012. The variation in hospitalization rates by age group evidenced a significant participation of men, young people and elderly women, allowing to conclude that hospital morbidity due to traffic accident not only increased but also affected young and elderly people. The results not only confirm the need to control the occurrence of these events but also suggest further studies.